COOPERATION BETWEEN KAZAKHSTAN AND RUSSIA WITHIN THE FRAMEWORK OF THE COLLECTIVE SECURITY TREATY - BAYZAKOVA, Kuralai (CENTRAL ASIA AND THE CAUCASUS, 2004)
In the new world order that has arisen since the collapse of the Soviet Union, the post-Soviet space has transformed into a new geopolitical and geostrategic field in which the current geopolitical situation is characterized by the major changes that have occurred in the world community since the end of the bloc opposition and the emergence of a new system of international relations. The threat of another world war and the use of nuclear and other types of weapons of mass destruction has been reduced, a multipolar world is continuously evolving, and immense improvements have been achieved in arms control and in strengthening stability and security throughout the world. At the same time, the global changes are also giving rise to contradictory factors. On the one hand, the international community is taking specific measures to expand cooperation and bring about the peaceful settlement of disputes, as well as put a harness on the arms race and the spread in nuclear weapons, while new risks and threats to security are arising, on the other. For the CIS countries, the same (or similar) main challenges have developed: international terror-ism, religious extremism, and the drug business, which the CIS states are trying to combat jointly in order to ensure regional security. The first attempt to create a mechanism which would embrace the entire post-Soviet space was the Collective Security Treaty (CST), signed on 15 May, 1992 by several CIS states.1 Pursuant to this document, the parties must coordinate their positions in this area. For example, Art 4 states that members of this structure should view aggression against one of the parties to the Treaty as aggression against all the members of the CST. And Art 1 stipulates that the member states of this organization should not enter any military alliances directed against any other country that is signatory to this document. At the same time, the Treaty permits its members to join collective security systems in Europe and Asia, and Art 10 leaves open the possibility for other states to join the Treaty.2 The CST is originally of a political and open nature and has no intention of forming a military bloc.t became the basis for a qualitatively new solution to the security problems of the member states by largely peaceful means, as well as for joining forces to form an essentially new security system. The signing of this document is a conscious step by several of the independent sovereign states that have newly arisen in the post-Soviet space aimed at enhancing their national security under the new geopolitical conditions. The Treaty is of special significance today, when the force factor is still very prevalent, only has changed its direction of focus. The CST guaranteed the fledgling independent states the necessary external conditions for independent nation-building and for conducting democratic and socioeconomic reforms and helped them to create their national armed forces and strengthen their defensibility.